Tianeptine enhances energy-related processes in the Hippocampal non-synaptic mitochondria in a rat model of depression - Peric, Ivana; Costina, Victor; Findeisen, Peter; Gass, Peter; Filipović, Dragana (Neuroscience, 2020)
Tianeptine (Tian) has been widely used in treating mood and anxiety disorders, and recently as a nootropic to improve cognitive performance. However, its mechanisms of action are insufficiently clear. We used a comparative proteomic approach to identify sub-proteome changes in hippocampal cytosol and non-synaptic mitochondria (NSM) following chronic Tian treatment (3weeks, 10mg/kg/day) of adult male Wistar rats and rats exposed to chronic social isolation stress (CSIS) (6weeks), an animal model of depression. Behavioural assessment of depressive and anxiety-like behaviours was based on sucrose preference, forced swim test and marble burying. Selected differently expressed proteins were validated by Western blot and/or immunohistochemical analysis. Tian normalized the behavioural alternations induced by CSIS, indicating its antidepressant and anxiolytic efficacy. Proteomic data showed that Tian increased the expression of proteasome system elements and redox system enzymes, enhanced energy metabolism and increased glyceraldehyde-3-phosphate dehydrogenase expression bound to NSM in control rats. Tian-treatment of CSIS-stressed rats resulted in a minor suppression of the increase in proteasome elements and antioxidative enzymes, except for an increase in Cu-Zn superoxide dismutase, and increased the level of Lactate dehydrogenase. Our results indicate on an increased NSM functionality in controls and suppression of the CSIS-induced impairment of NSM functionality by Tian treatment as well as on the CSIS-caused discrepancy in Tian effects relative to controls.